Ethics as Transverse Subject in Engineering Education: A Review of Current Efforts - Silva, Giuseppe S.; Vasconcelos, Pedro N.; Zambroni de Souza, Antonio C. (IEEE-RITA, 2025)
Engineering projects address society's demands and are multidisciplinary by nature. The occurrence of catastrophic failures and the imperative for responsible innovation evidence the importance of linking education with holistic solutions to complex global issues. However, integrating scientific and technological information with social demands has been increasingly neglected. In universities, the division of knowledge into independent subjects reinforces the principle of fragmentation, challenging the perception of problems in professional training. This manuscript advocates a transverse and transdisciplinary approach to teaching ethics in engineering to explore the role of future professionals as agents of socioeconomic and environmental transformation. The concept of transverse education emerges where a given discipline traverses disciplinary boundaries and is integrated into academic training without increasing the course curriculum. A rapid literature review is conducted to assess the current state of engineering ethics education and identify whether Transverse Education in Engineering Ethics (TEEE) is being applied in engineering academic institutions. Documents indexed by Web of Science and Scopus databases were considered in the review, complemented by a supplementary search to reduce the risk of geographical bias. Records were selected based on publication date, focus on engineering ethics education, and application maturity of TEEE according to international guidelines and the Brazilian National Common Curricular Base. Low worldwide adherence to TEEE is revealed, with 5% of the selected engineering teaching/learning records addressing ethics in a transversal manner. This article highlights the importance of TEEE and provides insights for integrating ethics into engineering education, serving as a tool for immediate application and future research.